Optimization of extrusion conditions for development of high quality rice-lupin-pumpkin based extruded snack food - Yeshambel Dagnaw Alefew; Abebaw Teshome Tiruneh; Tadesse Fenta Yehuala (Heliyon)
This study was examined to optimize extrusion conditions (barrel temperature, feed moisture, and blending ratios of rice, lupin, and pumpkin flour) during processing high-quality extruded products using a twin-screw extruder. A three-factor with three-level response surface methodology with a Box-Behnken design, was applied to evaluate the effects of selected processing conditions: blending ratios of lupin (10–20 %), barrel temperature (115–155 °C) and feed moisture content (14–20 %) on the functional, nutritional and sensory characteristics of the produced snack food. The independent variables significantly affected the nutritional, functional, and physical properties of the extruded snack food. A higher proportion of lupin showed higher bulk density but lower expansion ratio and water solubility index of the extrudates while higher feed moisture content led to a reduction in expansion ratio and water-soluble index of the extruded snack food. Lupin substitution and pumpkin flour addition significantly increased the protein, crude fiber, ash, fat, β-carotene, iron, and zinc contents of the white rice-lupin-pumpkin extruded snack, whereas the total carbohydrate content was reduced. The sensory evaluation showed that it was possible to incorporate lupin flour up to a certain level without affecting consumer acceptance. A blending ratio of 15 %, feed moisture of 14 %, and barrel temperature of 155 °C produced the extrudate with a desirability value of 0.75.